2009
DOI: 10.4055/jkoa.2009.44.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study for the Results of Unicompartmental Knee Arthroplasty in Patients Younger and Older than 60 Years of Age

Abstract: Purpose:We wanted to assess the relations between age and the outcome of unicompartmental knee arthroplasty (UKA) based on a comparative study of UKA patients younger than 60 years and UKA patients older than 60 years of age. Materials and Methods: Among the patients who underwent a UKA between January 2002 and June 2003, 230 cases (the group of patients with ages under sixty consisted of 89 knees -group I, and the group of patients with ages over sixty consisted of 141 knees -group II) were followed up for at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…On the clinical out comes of UKA in young patients (≤60 years), conflicting results have been reported in the literature. In recent studies, there is a growing tendency of showing promising outcomes of UKA com parable to those of TKA in young patients 1,13) . In 2017, Kim et al 14) reported successful midterm outcomes of UKA obtained in less than 60yearold young patients.…”
mentioning
confidence: 99%
“…On the clinical out comes of UKA in young patients (≤60 years), conflicting results have been reported in the literature. In recent studies, there is a growing tendency of showing promising outcomes of UKA com parable to those of TKA in young patients 1,13) . In 2017, Kim et al 14) reported successful midterm outcomes of UKA obtained in less than 60yearold young patients.…”
mentioning
confidence: 99%
“…On the clinical outcomes of UKA in young patients (≤60 years), conflicting results have been reported in the literature. In recent studies, there is a growing tendency of showing promising outcomes of UKA comparable to those of TKA in young patients 1 , 13) . In 2017, Kim et al 14) reported successful mid-term outcomes of UKA obtained in less than 60-year-old young patients.…”
mentioning
confidence: 99%